Interferência de vasodilatadores na hidrólise de nucleotídeos da adenina em plaquetas de pacientes hipertensos - Lunkes, Daniéle Sausen (2009)
The thrombogenic process that affects the hypertensive patient is associated with regulatory mechanisms present in the vascular endothelium. These mechanisms involve the release of a endothelium-derived relaxing factor, ectonucleotidases and calcium ions. Considering that vasodilators act both on blood pressure and on homeostasis, we evaluated the interference of different vasodilators on platelet NTPDase activity in hypertensive and healthy patients, with the objective of verifying patient sensitivity to vasodilators. In addition, the kinetic behavior of NTPDase was determined in the presence of the vasodilator that showed the greatest inhibitory influence. The results showed a decrease in NTPDase activity in the presence of arginine (0.025 mM 3.0 mM), sodium nitroprusside (0.01 mM 2.0 mM) and hydralazine (20.0 μM 90.0 μM), when tested for ATP and ADP substrate. However, the hydrolysis of ATP and ADP substrates increased when tested in the presence of arginine in the control group. No effects on enzyme activities were observed when pharmacological doses of captopril were tested in vitro. Kinetic behavior studies were estimated in the presence of sodium nitroprusside, which caused a mixed inhibition. The Km values increased and Vmax decreased with increasing sodium nitroprusside concentrations. The IC50 values were 3.66 mM and 2.64 mM (control group) and 2.08 mM and 3.15 mM (hypertensive group) for ATP and ADP, respectively. The Ki values obtained were 0.345 mM and 2.00 mM for the control group and 0.167mM and 0.325 mM for the hypertensive group, using ATP and ADP as substrate, respectively. In conclusion, based on these results it is possible to speculate that there is an interaction between vasodilators, donors of nitric oxide, and the inhibition of adenine nucleotide hydrolysis on platelets of hipertensive patients.